Correlation between Lung Asbestos Count at Necropsy and Radiological Appearances. Issue 5640 (8th February 1969) - Macpherson, Peter; Davidson, John K.
Abstract : In the first 100 of a series of 600 consecutive necropsies for which a chest x -ray film had been taken within a year of death the features of asbestosis were observed in eight of the nine cases where the asbestos count at subsequent necropsy exceeded 40. In only one of these cases had the diagnosis of asbestosis been suggested during life. The higher the asbestos count the greater the likelihood of radiographic abnormalities, particularly calcified and non-calcified pleural plaques on the chest wall and diaphragm.